2016
DOI: 10.1007/s00128-015-1719-x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Distribution of Carbamate Pesticides and Metalaxyl in Southern Ontario Surface Waters 2007–2010

Abstract: Surface water sampling in 2007–2010 measured the occurrence of carbamates and metalaxyl during base flow conditions and wet weather events in southern Ontario surface waters. Carbaryl, metalaxyl and pirimicarb were the most frequently detected compounds. In 2008 these three compounds were detected in over 50 % of the samples. Overall mean concentrations of carbaryl and metalaxyl over the course of the study (2007–2010) were 15 and 18 ng/L, respectively. Elevated concentrations of carbaryl (~100 to ~950 ng/L) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 2 publications
1
31
0
1
Order By: Relevance
“…All LC x values were greater than the maximum reported Ontario surface water concentrations for these investigated pesticides (Struger et al , ; National Pesticides Monitoring and Surveillance Network ), and the results from the present study indicated that both juvenile and adult L. siliquoidea were relatively insensitive to these pesticides at subchronic exposures, especially compared to effects on other nontarget organisms including aquatic insects (e.g., Prosser et al ; Raby et al ). Similar to the V. iris glochidia, juvenile and adult L. siliquoidea would be protected by proposed water quality guidelines (Table and Figures and ; Supplemental Data, Figures S1–S14).…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…All LC x values were greater than the maximum reported Ontario surface water concentrations for these investigated pesticides (Struger et al , ; National Pesticides Monitoring and Surveillance Network ), and the results from the present study indicated that both juvenile and adult L. siliquoidea were relatively insensitive to these pesticides at subchronic exposures, especially compared to effects on other nontarget organisms including aquatic insects (e.g., Prosser et al ; Raby et al ). Similar to the V. iris glochidia, juvenile and adult L. siliquoidea would be protected by proposed water quality guidelines (Table and Figures and ; Supplemental Data, Figures S1–S14).…”
Section: Resultssupporting
confidence: 51%
“…The present study reported the carbaryl EC50 for V. iris to be >6650 µg/L. The EC x values reported in the literature are substantially higher than concentrations for carbaryl in Ontario surface waters (Struger et al ). Lampsilis siliquoidea demonstrated a 96‐h EC50 to malathion of 23 000 µg/L (Wang et al ).…”
Section: Resultsmentioning
confidence: 39%
See 2 more Smart Citations
“…Therefore, the organochlorines are degraded very slowly and hence remain in the environment or/and inside the organisms after exposure for longer duration (Wandiga, 2001 ). Carbamates are derived from carbamic acid and used to kill insects/pests (Struger et al, 2016 ) in a similar fashion as organophosphates. It has been shown that carbofuran is highly neurotoxic and may modulate the functions of acetylcholinesterase (AChE) (Gupta et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%